Solvent-Free Synthesis of New 3';H-spiro[indole-3,2'-[1,3]]benzothiazole- 2(1H)-one Derivatives Using Michael Reaction - Zare, Zahra; Imanzadeh, Gholamhassan; Soltanzadeh, Zahra (Letters in Organic Chemistry, 2017)
Background: Benzothiazole is a heterocyclic compound, weak base and having various biological activities. This compound and its derivatives are widely found in bioorganic and medicinal chemistry with application in drug discovery. Spiro[indole-benzothiazoles] are one of analogs of the benzothiazole and isatin, having biological properties, such as anticancer and antioxidant. (15). The aim of this manuscript is to develop a green reaction for the synthesis of a new series of benzothiazole compounds using Michael addition reaction 3'H-spiro[indole-3,2'-[1,3]]benzothiazole-2(1H)-one to α,β-unsaturated esters under solvent-free conditions. Methods: 3'H-Spiro[indole-3,2'-[1,3]]benzothiazole-2(1H)-one and different acrylic and fumaric esters have been used to synthesize new derivatives of 3'H-Spiro[indole-3,2'-[1,3]]benzothiazole-2(1H)-one via aza-Michael addition amide nitrogen of 3'H-Spiro[indole-3,2'-[1,3]]benzothiazole-2(1H)-one to β-carbon atom of this α,β-unsaturated esters. These reactions were performed using K2CO3 (for single aza-Michael addition) and K2CO3 and tetrabutylammonium bromide (for double aza-Michael addition) at room temperature under solvent-free conditions. The structural assignments of the synthesized compounds were made on the basis of elemental analysis and spectroscopic data (IR, 1H NMR, 13C NMR and Mass). Results: The mono and bis-Michael adduct were synthesized using reaction between 3'H-Spiro[indole- 3,2'-[1,3]]benzothiazole-2(1H)-one and different acrylic esters in good to excellent yields (75%-95%). This reaction was performed in the presence of inorganic base K2CO3 and tetrabutylammonium bromide (for bis-Michael adduct) at room temperature under solvent-free conditions. Fumaric esters were unable to react with 3'H-Spiro[indole-3,2'-[1,3]]benzothiazole-2(1H)-one and produced no products. Conclusion: We developed a regioselective Michael addition reaction for the exclusive synthesis mono-Michael adduct in the presence of base K2CO3 under solvent-free conditions at room temperature. We have found that this selectivity disappears in the presence of TBAB under the same conditions. The present procedure has notable advantages, for example, simple operation procedure, environmentally benign reaction conditions, inexpensive and availability of the employed base catalyst.
Keywords: Tetrabutylammonium bromide